Pembelajaran Hybrid pada Literasi Digital dalam Implementasi Kurikulum Merdeka - Supriyadi, Supriyadi (Jurnal Inovasi Pendidikan MH Thamrin, 2022)
In the 21st century, the presence of information and communication technology that is quite modern is increasingly rooted in every human life. This study aims to reveal Hybrid Learning Against Digital Literacy in the Implementation of the Independent Curriculum for Madrasah Students This research is a quantitative research with a survey approach. The population in this study were all students of Madrasah Aliyah Negeri 2 East Jakarta, totaling 305 students. The number of research samples refers to the Isaac & Michael table with a significance of 5% as many as 161 students taken randomly. Research data obtained through valid and reliable instruments. The results of the study can be concluded 1) Hybrid learning has a positive effect on Digital Literacy in the Implementation of the Student's Independent Curriculum; 2) Regression Y or X is significant or Hybrid learning has a positive effect on Digital Literacy in the Implementation of the Student's Independent Curriculum; 3) The correlation coefficient of X and Y is significant or significant. While the coefficient of determination from the table above can be seen in the 2nd row, namely R Square = 0.231, which means that 23.1% of the variation in digital literacy variables is influenced by hybrid learning